The Identity of Baan Wang sai Community Tham Yai Sub-district, Thung Song District, Nakhon Si Thammarat Province - Unjan, Rattana; Phetchit , Jareporn; Buakhao, Sathit (Ratchaphruek Journal, 2021)
This research was the study of the identity of Ban Wang Sai. The purposes were: 1) To study some of the economic and social background information related to the identity of Ban Wang Sai community; 2) To study the identity of the Ban Wang Sai community in 3 aspects: social aspect, participation Environment; 3) To study the factors affecting the identity of Ban Wang Sai community; and 4) To study the suggestion from a total of 34 consumers. The collected data were analyzed by the ready-made social science statistics program including percentage, mean, standard deviation and Multiple Regression. The research results showed that most of the participants were farmers who belief in sacred things. A community’s peculiarity was the abundance of resources. The identity of Ban Wang Sai community, it was found that social identity was at a high level (4.18), participation identity was at the highest level (4.77), and environmental identity was at the highest level (4.71). The results of the hypothesis testing also revealed that social identity, participatory identity and environmental identity had a statistically significant effect on community identity .01 It was suggested that training and knowledge should be provided to people in the community and there should be suggestions and support from the government.